2021
DOI: 10.3390/ijerph18031080
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Version of the Nursing Profession Self-Efficacy Scale: A Methodological Study

Abstract: Background: The Nursing Profession Self-Efficacy (NPSE) scale was developed to reflect the characteristics of nursing tasks. This study was conducted to validate the Korean version of the NPSE (K-NPSE) scale. Methods: The NPSE scale with nineteen items was translated into Korean after forward and backward translation according to Devellis’ guideline. For the exploratory factor analysis (EFA), 298 nurses participated and criterion-related validity and reliability were verified. For the confirmatory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The original NPSES developed by Caruso et al (2016) [ 24 ] includes two factors: ‘quality of service’ and nursing ‘professional situations’; these factors measure the skills nurses need to work in professional ways. Our study is more similar to a previous study located in Korea [ 45 ] and defined four factors in the A-NPSES.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The original NPSES developed by Caruso et al (2016) [ 24 ] includes two factors: ‘quality of service’ and nursing ‘professional situations’; these factors measure the skills nurses need to work in professional ways. Our study is more similar to a previous study located in Korea [ 45 ] and defined four factors in the A-NPSES.…”
Section: Discussionsupporting
confidence: 86%
“…We developed a fit model using CFA that showed that a four-factor structure explained the data collected from our reference sample better than the original two-factor model. Surely, the differences in the characteristics of the sample analyzed and the different cultural contexts are attributable to different nursing environments and may explain the differences in the structure of the factors, as they also indicated in the study of the Korean researchers, where even the structure of NPSES in the Korean context was to four factors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following are considered the reasons for this result: First, although 150 participants were considered eligible to participate, only 126 participants were included in this study. Second, to ensure the accuracy of CFA analysis, independent collection of data that do not overlap with EFA data is required [43,44]. However, the same data were analyzed for both CFA and EFA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although having specific scales is vital to exploring the specific relationships between task-specific self-efficacy and related outcomes, having a broader measure of nursing self-efficacy is also essential when establishing a relationship with broader outcomes (e.g., stress, burnout, and job dissatisfaction) and requires further research [19]. The most widely used self-report scale is the Nursing Profession Self-Efficacy Scale (NPSES), developed in 2016 and translated into several languages (e.g., Korean, Albanian, Turkish) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%